The relationship between physical activity and the risk of diabetes mellitus in elementary school children (ages 8–12 years) - Bimantari, Rafina; Astuti, Erlina Suci (Science Midwifery, 2025)
The rapid advancement of technology and shifts in modern lifestyles have led young children to spend more time indoors engaging with electronic devices, consequently reducing their physical activity levels. Insufficient physical activity during early childhood is considered a potential risk factor for developing Diabetes Mellitus (DM). This study aimed to investigate the relationship between physical activity and the risk of DM among elementary school children aged 8–12 years. A cross-sectional quantitative design was employed in May 2025 at SDN Tasikmadu 1 Malang, involving 154 participants within the specified age range. Data were analyzed using the Chi-Square test. The results indicated that 84.4% of the children demonstrated a moderate level of physical activity, while 15.6% exhibited a high level. Regarding diabetes risk, 43.5% were classified as moderate risk, 37.0% as low risk, and 19.5% as high risk. Statistical analysis revealed no significant association between physical activity and diabetes risk (p = 0.294, p > 0.05). In conclusion, there was no statistically significant relationship between physical activity and DM risk among the studied population. Nevertheless, regular monitoring and the promotion of physical activity remain essential to support overall child health and reduce the likelihood of future metabolic disorders.